Co-modification of corn flour by Lactobacillus HR and transglutaminase reduces glycemic index and enhances functional properties - Xu, Xingda; Guo, Yifan; Sun, Hongdi; Zhang, Yutong; Yang, Wanting; Zheng, Hua; Xu, Lei; Wang, Yan (Frontiers in Nutrition, 2026)
IntroductionThe complex protein structure, high glycemic index (GI), coarse taste and poor formability of corn significantly hinder its deep processing performance and represent key technical bottlenecks in the industrialization of corn-based food products.MethodsIn this study, co-modification with optimized lactic acid bacteria (Lactobacillus HR) and transglutaminase (TGase) effectively converted corn flour into a low-glycemic index (GI) product, primarily due to flour’s high starch content.ResultsThe results revealed that fermentation under the optimum circumstances (36.83 °C, fermentation time of 49.25 h, inoculum level of 1.03 × 108 CFU/mL, and enzyme dosage of 2.58‰) produced flour with significant nutritional improvements. Co-modification yielded the lowest GI (48.87) and enhanced the nutritional profile, with increased soluble protein content (5.96  mg/g) and resistant starch levels (51.19%). FTIR analysis revealed an increase in the (1047/1022) cm−1 absorbance ratio, suggesting a higher degree of starch molecular order and consequently, enhanced resistance to enzymatic digestion. Compared with untreated corn flour, the treated samples showed a 10.3% decrease in water-holding capacity and a 29.7% increase in gel strength.ConclusionThe co- modification of Lactobacillus HR and TGase caused a more compact internal structure, which further reduced the hydrolyzability of corn starch. Based on the above results, this study indicates that the integrated biological treatment is a feasible method for improving the nutritional quality and functional properties of cereal flours.